Dannye k rekonstrukcii balto-slavjanskogo pohoronnogo obrjada: kašub. donota »moloko« (leksiko-semantičeskie paralleli balto-slavjanskogo areala)The Data to Reconstruction of the Baltic-Slavic Funeral Ceremony: Kashubian donota »milk« (Baltic and Slavic Lexical Equivalents) - Kregždys, Rolandas (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article deals with the authenticity of evaluation of ancient Slavic and Baltic religion archetypes. By means of internal reconstruction and typology methods, the work is supplemented by the new analysis of the Kashubian donota »milk« and its possible Baltic and Slavic lexical equivalents: Pruss. dadan »milk«, toponym West Slav. Dadowe. Recently some attempts were undertaken to reinstate the new mythological elements which require verifi cation in-depth, since such innovations are frequently founded only on the researcher’s guesses and erroneous elucidation of the linguistic data.